Kinetic analysis of peptide loading onto HLA-DR molecules mediated by HLA-DM. - Vogt, Anne B.; Kropshofer, Harald; Moldenhauer, Gerhard; Hämmerling, Günter J. (Proceedings of the National Academy of Sciences of the United States of America, 1996)
The nonclassical major histocompatibility complex class II molecule HLA-DM (DM) has recently been shown to play a central role in the class II-associated antigen presentation pathway: DM releases invariant chain-derived CLIP peptides (class II-associated invariant chain protein peptide) from HLA-DR (DR) molecules and thereby facilitates loading with antigenic peptides. Some observations have led to the suggestion that DM acts in a catalytic manner, but so far direct proof is missing. Here, we investigated in vitro the kinetics of exchange of endogenously bound CLIP for various peptides on DR1 and DR2a molecules: we found that in the presence of DM the peptide loading process follows Michaelis-Menten kinetics with turnover numbers of 3-12 DR molecules per minute per DM molecule, and with KM values of 500-1000 nM. In addition, surface plasmon resonance measurements showed that DM interacts efficiently with DR-CLIP complexes but only weakly with DR-peptide complexes isolated from DM-positive cells. Taken together, our data provide evidence that DM functions as an enzyme-like catalyst of peptide exchange and favors the generation of long-lived DR-peptide complexes that are no longer substrates for DM.